Central deafness: a review of past and current perspectives. (3rd October 2019) - Musiek, Frank E.; Chermak, Gail D.; Cone, Barbara
Abstract: Objective: The purpose of this review was to describe and differentiate clinical syndromes caused by lesions of the central auditory nervous system (CANS). Design: Relevant literature was identified through Pubmed and Google Scholar searches using the key terms: central deafness, auditory agnosia, word deafness and cortical deafness. Given the authors' intent to review past and current perspectives on central deafness, no publication date range was imposed. Study sample: The review is organised around complete central deafness (CCD), central deafness (CD), word deafness and nonverbal agnosia (NVA), including anatomy and pathophysiology, symptom profile and audiological findings. Four case studies are presented to demonstrate the clinical correlates of CD. Conclusions: Central deafness is a rare condition typically resulting from bilateral compromise of the CANS. The closer to the auditory cortex bilateral lesions are located, the greater the probability of CD. A variety of symptoms present with or appear subsequent to CD, including tinnitus, hallucinations, voice changes and hypersensitivity to sounds (if heard by the patient), as well as diverse neurological symptoms depending on the non-auditory areas of the brain that may also be involved. Thorough and appropriate audiological testing is critical to accurately diagnose CD and its variants.